2019
DOI: 10.1002/clc.23167
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular block can be used as a risk predictor of clinical atrial fibrillation

Abstract: Background Atrial fibrillation (AF) is the most common cardiac arrhythmia, with its incidence making up nearly one‐third of all hospital admissions. Atrioventricular block (AVB) is a conduction abnormality along the atrioventricular node or the His‐Purkinje system. The relationship between atrioventricular conduction block and AF is controversial. Hypothesis This study is designed to observe whether there is a correlation between AVB and AF, and which type of AVB has th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Regarding the association of second‐ or third‐degree atrioventricular block and AF, the data are sparse. Recently, in a retrospective analysis, Zhao et al showed that all three main types of atrioventricular block are associated with AF 5 . Moreover, in a small study of 81 patients over 70 years old, with no AF history, who were implanted a pacemaker owing to complete heart block, 65% developed AHRE with duration >5 min after 18 months of follow‐up 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the association of second‐ or third‐degree atrioventricular block and AF, the data are sparse. Recently, in a retrospective analysis, Zhao et al showed that all three main types of atrioventricular block are associated with AF 5 . Moreover, in a small study of 81 patients over 70 years old, with no AF history, who were implanted a pacemaker owing to complete heart block, 65% developed AHRE with duration >5 min after 18 months of follow‐up 6 .…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In fact, tachy-brady syndrome is a very frequent manifestation of SND. On the other hand, the evidence linking second-or third-degree atrioventricular block with AF is less robust, 5 while atrial high-rate episodes (AHRE) and AF observed after the implantation of a pacemaker in these patients may be associated with new-onset heart failure/pacing-induced cardiomyopathy. 6,7 The pathophysiology of atrial remodeling is very complex, and the molecular pathways implicated in the initiation and perpetuation of AF show a high diversity and variability across different underlying substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Fusion between A3 and A4 may occur during sinus tachycardia; thus, limiting rate increase and exercise tolerance. Body movement can interfere with A4 sensing, as well as frequent PVCs [98]. Rate smoothing can mitigate transient atrial undersensing: assuming a regular atrial activation, pacing occurs for a brief period also when A4 signal is hampered.…”
Section: Leadless Cardiac Stimulation: Anothermentioning
confidence: 99%
“…Inherited progressive cardiac conduction disease (PCCD) is defined as an abnormal progressive cardiac conduction disorder [1], in which atrioventricular block (AVB) is characteristic by the presence of heart conduction block between atria and ventricle on 12-lead electrocardiogram (ECG). This abnormality of cardiac conduction will elevate the risk of sudden cardiac death, which will become a heavy burden for both family and society [2][3][4]. AVB can be classified into three tiers according to the extension degree and ECG.…”
Section: Introductionmentioning
confidence: 99%